2017
DOI: 10.1016/j.ajodo.2016.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Root resorption of maxillary incisors retracted with and without skeletal anchorage

Abstract: Although the root resorption degree of the skeletal anchorage group was not significantly different from the group without skeletal anchorage, the number of patients with severe to extreme resorption in the first group was significantly greater. Therefore, careful clinical monitoring of skeletally anchored anterior retraction is needed, especially when there are known root resorption predisposing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 80 publications
1
9
0
3
Order By: Relevance
“…A prospective study comparing RR with and without skeletal anchorage warranted its use in patients requiring maximum retraction. 16 However, on assessing their classification into slight-to-moderate and severeto-extreme RR, a significantly higher percentage of patients treated with skeletal anchorage experienced severe to extreme RR (47%)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prospective study comparing RR with and without skeletal anchorage warranted its use in patients requiring maximum retraction. 16 However, on assessing their classification into slight-to-moderate and severeto-extreme RR, a significantly higher percentage of patients treated with skeletal anchorage experienced severe to extreme RR (47%)…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the conclusions derived from the current study present a higher level of evidence that may be applicable clinically. A prospective study comparing RR with and without skeletal anchorage warranted its use in patients requiring maximum retraction 16 . However, on assessing their classification into slight‐to‐moderate and severe‐to‐extreme RR, a significantly higher percentage of patients treated with skeletal anchorage experienced severe to extreme RR (47%) when compared to patients treated with conventional anchorage (18%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar finding was found in other studies. 13,17 Few studies 17,19,20 found that the maxillary central incisors were the most resorbed, with 27% undergoing greater than 1 mm of root resorption and premolars and canines were relatively unaffected. Proximity between the roots of maxillary central incisors and the cortical bone of the socket, the incisive canal and the alveolar bone on the buccal surface, combined with the type of movement may explain the higher incidence of severe root resorption these teeth.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of these devices may depend on patient cooperation, cause discomfort and other problems, and produces limited efect [2,3]. Miniscrew implants are considered to achieve maximum anchorage control [4], but the risks of fracture, expulsion, damage to adjacent tissues, and root and alveolar bone absorption have been reported [5][6][7], which are also expensive. Terefore, methods to safely, comfortably, simply, and efectively enhance anchorage are urgently needed.…”
Section: Introductionmentioning
confidence: 99%